Promotion of Tourism Area of Pangandaran Regency through Instagram Social Media Accounts - Muhammad Yuka Afryantono; Cinthia Kusuma Rani; Angelia Salim (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2022)
This study aims to understand the use of Instagram social media as a medium for tourism promotion in Pangandaran Regency through the @explorepangandaran and @berandapangandaran accounts.  For the reasons @explorepangandaran and @berandapangandaran accounts are used as tourism promotion media in Pangandaran Regency. This research uses  a qualitative research method with a case study approach. Based on observations and interviews conducted, the results of the study show that tourism activists use Instagram social media as the only medium in carrying out promotional activities. The explore feature is to expand the reach of the promotion through the use of the hashtags (#)explorepangandaran and (#)berandapangandaran. Through this hashtag, tourism activists can produce  promotional content. The @explorepangandaran and @berandapangandaran accounts are promotional accounts that are managed independently by tourism activists. In addition, these two accounts have advantages in terms of engagement compared to other tourism promotion methods.